Sexual dysfunction and fertility-related distress in young adults with cancer over 5 years following diagnosis: study protocol of the Fex-Can Cohort study - Wettergren, L. (BMC Cancer, 2020)
BACKGROUND: There is a lack of firm knowledge regarding sexual problems and fertility-related distress in young adults following a diagnosis with cancer. Establishing such understanding is essential to identify patients in need of specific support and to develop cancer care accordingly. This study protocol describes the Fex-Can Cohort study, a population-based prospective cohort study investigating sexual dysfunction and fertility-related distress in young adults diagnosed with cancer in Sweden. The primary objective of the study is to determine the prevalence and predictors of sexual dysfunction and fertility-related distress following a cancer diagnosis in young adulthood compared to prevalence rates for the general population. Further aims are to investigate the trajectories of these issues over time, the co-existence between sexual dysfunction and fertility-related distress, and the relation between these issues and body image, anxiety and depression, health-related quality of life, self-efficacy related to sexuality and fertility, and fertility-related knowledge. METHODS: Participants in the Fex-Can Cohort will be identified via the Swedish National Quality Registries for Brain Tumors, Breast Cancer, Gynecological Oncology, Lymphoma, and Testicular Cancer. All patients diagnosed at the ages of 18–39, during a period of 18 months, will be invited to participate. Established instruments will be used to measure sexual function (PROMIS SexFS), fertility-related distress (RCAC), body image (BIS), anxiety and depression (HADS), and health-related quality of life (QLQ-C30); Self-efficacy and fertility-related knowledge will be assessed by study-specific measures. The survey will be administered to participants at baseline (approximately 1.5 year after diagnosis) and at 3 and 5 years post-diagnosis. Registry data will be used to collect clinical variables. A comparison group of 2000 young adults will be drawn from the Swedish population register (SPAR) and subsequently approached with the same measures as the cancer group. DISCUSSION: The study will determine the prevalence and predictors of sexual dysfunction and fertility-related distress in young men and women with cancer. The findings will form a basis for developing interventions to alleviate sexual problems and fertility-related distress in young adults with cancer in the short and long term. TRIAL REGISTRATION: This is an observational cohort study and clinical trial registration was therefore not obtained.